2020
DOI: 10.3847/1538-4357/ab7eb1
|View full text |Cite
|
Sign up to set email alerts
|

Fluorine in the Solar Neighborhood: The Need for Several Cosmic Sources

Abstract: The cosmic origin of fluorine is still not well constrained. Several nucleosynthetic channels at different phases of stellar evolution have been suggested, but these must be constrained by observations. For this, the fluorine abundance trend with metallicity spanning a wide range is required. Our aim is to determine stellar abundances of fluorine for −1.1 < [Fe/H] < +0.4. We determine the abundances from HF lines in infrared K-band spectra (∼ 2.3 µm) of cool giants, observed with the IGRINS and Phoenix high-re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 60 publications
5
46
0
Order By: Relevance
“…Mishenina et al (2015) instead reintroduced the intermediate neutron-capture i-process discussed earlier by Cowan & Rose (1977) to explain this fact, in which the neutron density operating the process is approximately 10 15 cm −3 . Also, recently Ryde et al (2020) found a secondary behaviour of [F/Fe] for supersolar metallicities in K giants. We note that F has a significant cosmic contribution from AGB stars (Jorissen et al 1992;Karakas & Lattanzio 2014;Abia et al 2019).…”
Section: Comparison With Gce Modelsmentioning
confidence: 89%
“…Mishenina et al (2015) instead reintroduced the intermediate neutron-capture i-process discussed earlier by Cowan & Rose (1977) to explain this fact, in which the neutron density operating the process is approximately 10 15 cm −3 . Also, recently Ryde et al (2020) found a secondary behaviour of [F/Fe] for supersolar metallicities in K giants. We note that F has a significant cosmic contribution from AGB stars (Jorissen et al 1992;Karakas & Lattanzio 2014;Abia et al 2019).…”
Section: Comparison With Gce Modelsmentioning
confidence: 89%
“…In a detailed study of the uncertainties in the nuclear reaction rates for 19 F, Lugaro et al (2004) concluded that these cause uncertainties in theoretical models of fluorine production of a factor of 2-7, depending on the initial stellar mass. A recent study by Ryde et al (2020) argues for multiple sites of fluorine production, in particular at different metallicities. Nevertheless, it has been clear for some time that AGB stars play a significant role in the production of fluorine.…”
Section: Abundance Of Fluorinementioning
confidence: 99%
“…A diagnostic is via observations of molecular HF emission lines in the K and N bands (2.1-2.4 µm and 8-13 µm, respectively), which are observable only in cool giants (T eff < 4500 K). Analysis of the spectra of K giants show that the fluorine-to-oxygen abundance ratio [F/O] increases as a function of oxygen abundance [O/H] with a slope 1±0.2, and can reach [F/O]≈0.4 dex for [O/H]≈0.2 dex (Ryde et al 2020). Behavior like this is typical for the so-called "secondary" elements, whose synthesis in stars involves nuclides pre-existing in the ISM gas of which stars form.…”
Section: Primary Fluorinementioning
confidence: 99%
“…Novae are also proposed as a possible source of fluorine through proton captures by 17 O. A useful review of fluorine nucleosynthesis is given in Ryde et al (2020).…”
Section: Primary Fluorinementioning
confidence: 99%